2022
DOI: 10.3390/medicina58020287
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic, Professional and Institutional Characteristics That Make Romanian Doctors More Prone to Malpractice Complaints

Abstract: Background and objectives: Medical malpractice is a phenomenon that shadows current medical practice, the number of complaints following an upward trend worldwide. The background for complaints is related both to the doctor and medical practice in general, as well as to the patient. The aim of this study was to identify a profile of the Romanian doctors who are more prone to receiving complaints, by analyzing the socio-demographic, professional and institutional characteristics. Materials and Methods: We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Additionally, we identified a gap between physicians who work entirely in the public sector and those who work in both the public and private sectors, implying that the private sector exposes physicians to additional legal standards. This could be attributed to the fact that private-sector Romanian physicians are more prone to be accused of medical malpractice, according to a recent study [17]. Results indicate that physicians are aware of the patient's right to informed consent but lack comprehensive understanding.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, we identified a gap between physicians who work entirely in the public sector and those who work in both the public and private sectors, implying that the private sector exposes physicians to additional legal standards. This could be attributed to the fact that private-sector Romanian physicians are more prone to be accused of medical malpractice, according to a recent study [17]. Results indicate that physicians are aware of the patient's right to informed consent but lack comprehensive understanding.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the likelihood of being married is higher in this age group, potentially increasing the importance of malpractice risk due to added responsibilities. For example, a study conducted in Romania identified gender, working more shifts, and being married to a spouse in the same specialty as distinctive factors influencing physicians' concerns regarding malpractice complaints [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Soh and colleagues [ 11 ] identified a correlation between malpractice incidents and prolonged work hours in their studies. Hanganu and colleagues [ 12 ] emphasized that night shifts similarly elevate stress, fatigue, and risk, similar to extended work hours.…”
Section: Introductionmentioning
confidence: 99%
“… * This study is part of a larger doctoral research, and the same group of participants was analyzed in a different paper, from a different perspective, published somewhere else [ 14 ]. 1 Number of answers (N), percentage (%), mean value (M), and standard deviation (SD).…”
Section: Figurementioning
confidence: 99%